The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/tp.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

Complex epigenetic regulation of Engrailed-2 (EN-2) homeobox gene in the autism cerebellum

Abstract: The elucidation of epigenetic alterations in the autism brain has potential to provide new insights into the molecular mechanisms underlying abnormal gene expression in this disorder. Given strong evidence that engrailed-2 (EN-2) is a developmentally expressed gene relevant to cerebellar abnormalities and autism, the epigenetic evaluation of this candidate gene was undertaken in 26 case and control post-mortem cerebellar samples. Assessments included global DNA methylation, EN-2 promoter methylation, EN-2 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 64 publications
2
75
0
Order By: Relevance
“…[34] Increased histone H3K4 trimethylation and decreased histone H3K27 trimethylation are observed in the engrailed-2(EN-2) homeobox gene in the autism samples, which is a gene relevant to cerebellar abnormalities and autism. [35] Recent studies have found that many ASD associated genes, for example, oxytocin receptor gene (OXTR), Glutamate decarboxylase 1 (GAD1), and Engrailed-2 (EN2), exhibited altered DNA methylation and demethylation status. [35][36][37] During neuronal development of human, DhMRs (differentially hydroxymethylated regions) well overlap with FMR1 regulated genes, and autism related genes.…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Increased histone H3K4 trimethylation and decreased histone H3K27 trimethylation are observed in the engrailed-2(EN-2) homeobox gene in the autism samples, which is a gene relevant to cerebellar abnormalities and autism. [35] Recent studies have found that many ASD associated genes, for example, oxytocin receptor gene (OXTR), Glutamate decarboxylase 1 (GAD1), and Engrailed-2 (EN2), exhibited altered DNA methylation and demethylation status. [35][36][37] During neuronal development of human, DhMRs (differentially hydroxymethylated regions) well overlap with FMR1 regulated genes, and autism related genes.…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
“…[35] Recent studies have found that many ASD associated genes, for example, oxytocin receptor gene (OXTR), Glutamate decarboxylase 1 (GAD1), and Engrailed-2 (EN2), exhibited altered DNA methylation and demethylation status. [35][36][37] During neuronal development of human, DhMRs (differentially hydroxymethylated regions) well overlap with FMR1 regulated genes, and autism related genes. [38] Interestingly, Tet1 expression increases in autistic brain of human and increased enrichment of 5hmC at the promoters of RELN and GAD1 is associated with autism.…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
“…• Methylation level of specific genes in nonsyndromic ASD: The postmortem brain tissues from ASD patients show increased DNA methylation within the genes of: oxytocin receptor (OXTR) [163], RORA [164], Engrailed-2 (EN2) homeobox gene [165], Reelin (RELN) [166], and BCL2 gene [167].…”
Section: Mendelian Asd Disorders In Dna Methylation Machinerymentioning
confidence: 99%
“…Engrailed homeobox 2 (EN2) is a homeobox gene that is critical to the development of the midbrain and cerebellum [49]. It regulates the combined processes of cell division, differentiation and organ development.…”
Section: Pathway Genesmentioning
confidence: 99%